2010
DOI: 10.1080/10610271003763263
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced liquid–liquid anion exchange using macrocyclic anion receptors: effect of receptor structure on sulphate–nitrate exchange selectivity

Abstract: When certain macrocyclic anion receptors are added to a chloroform solution of the nitrate form of a lipophilic quaternary ammonium salt (methyltri-C 8,10 -ammonium nitrate, Aliquat 336N), the extraction of sulphate from an aqueous sodium nitrate solution via exchange with the organic-phase nitrate is significantly enhanced. Eight macrocycles were surveyed, including two derivatives of a tetraamide macrocycle, five derivatives of calix[4]pyrrole and b-decafluorocalix [5]pyrrole. Under the hypothesis that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Previously, we observed that the addition of 1 to methyltrialkyl(C 8-10 )ammonium nitrate (2aÁNO 3 , Aliquat s 336N) in chloroform resulted in enhanced exchange for sulfate (SO 4 2À ) from a solution of sodium nitrate as measured by an increase in the sulfate distribution ratio (D SO 4 = [SO 4 2À ] org /[SO 4 2À ] aq ). 7 Equilibrium modeling showed that the enhanced exchange corresponds to a shift to the right in the Scheme, nitrate binding being relatively weak. 7 Unexpectedly, enhancement with 1 was stronger than with its betaoctafluorinated analog, which normally binds anions much more strongly in aprotic organic solvents, presumably owing to stronger hydrogen-bond (H-bond) donation than 1.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Previously, we observed that the addition of 1 to methyltrialkyl(C 8-10 )ammonium nitrate (2aÁNO 3 , Aliquat s 336N) in chloroform resulted in enhanced exchange for sulfate (SO 4 2À ) from a solution of sodium nitrate as measured by an increase in the sulfate distribution ratio (D SO 4 = [SO 4 2À ] org /[SO 4 2À ] aq ). 7 Equilibrium modeling showed that the enhanced exchange corresponds to a shift to the right in the Scheme, nitrate binding being relatively weak. 7 Unexpectedly, enhancement with 1 was stronger than with its betaoctafluorinated analog, which normally binds anions much more strongly in aprotic organic solvents, presumably owing to stronger hydrogen-bond (H-bond) donation than 1.…”
mentioning
confidence: 98%
“…The enhancement of liquid-liquid anion-exchange selectivity by an anion receptor (R) can be usefully viewed as a standard anion-exchange equilibrium modified by competitive coordination of the exchanging anions by R. 7 Enhanced exchange of a univalent anion (X À ) by a divalent anion (Y 2À ) in the presence of a lipophilic cation (Q + ) and R may be illustrated in the following Scheme (for the case of predominant organicphase ion-pairing):…”
mentioning
confidence: 99%
See 3 more Smart Citations